Komplikasi Bedah, Luaran Fungsi Seksual dan Menstruasi dari Prosedur Vaginoplasti Sigmoid pada Pasien dengan Agenesis Vagina - Roy Jansen Sinaga; Nuring Pangastuti; Ova Emilia (JURNAL KESEHATAN REPRODUKSI, 2020)
Background:  Vaginal agenesis is one form of abnormality found in the uroginecology with a prevalence of 1: 4000 births. Various reconstruction techniques, both non-surgical and surgical, have been introduced, one of which is sigmoid vaginoplasty. Research on the complications and outcomes of sigmoid vaginoplasty procedure is still limited.Objective: To assess surgical complications, sexual and menstrual function outcomes of sigmoid vaginoplasty procedure.Method: This is a prospective study. A total 11 patients with a variety of genital tract malformations have been performed for sigmoid vaginoplasty during January 2017 to January 2019. Data are described descriptively-analytically. All patients were assessed for surgical complications, menstrual and sexual function after surgery.Results and Discussion: A total of 10 cases (90.9%) were diagnosed with vaginal agenesis and 1 case (9.1%) was diagnosed with Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome. Durante surgery complications are severe bleeding and rectum injury, occurred in 2 cases (18.2%). Postoperative complication is surgical wound dehiscence, occurred in 2 cases (18.2%). All patients who have uterus (100%) showed good menstrual function outcomes. Of the 3 married patients, all patients (100%) showed good postoperative sexual function outcomes (FSFI score 27-30.4). Conclusion: The sigmoid vaginoplasty procedure is an effective procedure for patients with agenesis vaginal. This procedure has low surgical complications with good outcomes of menstrual and sexual function. Keywords: Sigmoid vaginoplasty; vaginal agenesis; menstrual function; sexual function.